Semiotics Analysis of Human Value in the Film "The Giver" - Doni Anggoro Ari Santoso; Rofiq Noorman Haryadi; Maharanny Setiawan Poetri; Irfan Rifai; Denok Sunarsi (Jurnal Sinestesia, 2023)
The purpose of this study is to analyze how the value of humanity in the film The Giver uses Roland Barthes' semiotic analysis approach. Described structured and conceptualized to be able to obtain valid and easy to understand data. The description of the data and the explanation of the aspects of the keywords above form a description of the information on research findings in order to obtain the concept of analysis regarding the human value that is to be sought for its existence. This research also aims to provide education and new insights about films that have messages and concepts about life that are different from usual. The film The Giver was chosen because it was deemed sufficient to have criteria as a film that deserves to be analyzed because it has a storyline and sketches of life that are anti-mainstream from others. This research uses semiotic analysis of Roland Barthes who studies the signs that will describe the denotative, connotative and mythical meanings of the story. This film analysis research process requires a high level of focus and commitment in order to obtain the conclusion data to be achieved. The results of this study illustrate how the human values in the film The Giver are not applied or violate human norms which are the fundamentals of a human's life.